Tax return as a political statement - Alexander Libman; André Schultz; Thomas Graeber (Frankfurt School of Finance & Management, 2011)
The accuracy of a tax return is usually interpreted as an outcome of the tax evasion decision by an individual. However, in non-democratic regimes with predatory blackmail tax systems it is possible that large sums voluntarily reported by influential politicians or businessmen may be used as political statements. By openly acknowledging one's personal income an individual can signal the strength of one's position, or, on the contrary, the submissiveness to the political leadership. In this paper we explore the idea of the tax return as a political statement and test it using a unique dataset of the tax returns filed by the Russian regional governors and the members of their families for the year 2009. Our results conjecture that Russian governors may deliberately file their tax return as a political statement to signal their strength vis-à-vis the central government.
Keywords: D73; D78; H26; P26; 330; tax compliance; communication in non-democracies; Russian regions; Steuermoral; Steuererhebung; Politik; Normbefolgung; Regionalverwaltung; Public Choice; Russland